Mekanisme Kekerasan terhadap Perempuan dalam Rumah Tangga Perspektif Teori Kekerasan Simbolik Pierre Bourdieu - Musarrofa, Ita (UIN Sunan Kalijaga, 2015)
This article examines the theoretical perspective of Pierre Bourdieu, a French sociologist, in uncovering the mechanisms of domestic violence against women. Bourdieu initiated the theoretical tools, such as the theory of habitus, capital, arena, violence and symbolic power that can be used to dismantle the mechanisms of violence against women in the household. The occurrence of various forms of domestic violence against women, according to Bourdieu's theory, cannot be separated from the symbolic violence that became the basis for the formation of other types of violence, such as physical, psychological, economic, and sexual violence. Symbolic violence is violence in its most refined. This Violence is working through language symbols for herding them who is dominated to follow the meaning that are produced based on the interests of the dominant. This violence occurs due to the use of habitus that placing women as second-class beings in society and the women poverty off our composition of capital that should be played in the domestic arena, i.e. economic, cultural, social and symbolic capital. This violence, that work sat the level of knowledge, will not make women complain about the use of violence they experienced in the household. In contrast, women will receive and consider the violence they experienced as are ward field.